Piloting a framework to explore the impacts of public health workforce capacity-building initiatives - Frost, Cheyanna; Lawless, Jeanne W.; Leong, Donna; Meredith, Genevive R. (Frontiers in Public Health, 2025)
IntroductionTo reinforce and re-build the public health workforce, many capacity building interventions are in place. While pre-post assessments are often used to describe short-term outcomes, methods to assess and describe longer-term outcomes and impacts are wanting. Our work aimed to help close this gap by exploring ways to assess and describe longer-term outcomes, including how capacity gains contribute to new actions taken by individual workers and organizations in support of public health goals. We hoped this work might inform development of an evaluation framework able to measure outcomes and impacts of public health workforce capacity-building initiatives.MethodsBuilding from short-term outcomes data demonstrating changes in participant capacity (knowledge, skill, confidence), we used a multiple case study design to explore outcomes resulting from the use of the online Public Health Essentials (PHE) capacity building intervention. We conducted in-depth interviews with a purposive sample of eight PHE graduates (Summer 2023-Spring 2024) to elucidate both medium-term outcomes and potential longer-term impacts. Qualitative interviews were coded and analyzed using a priori and emergent themes (Spring-Fall 2024).ResultsInterview analysis revealed outcomes grouped into 13 themes. PHE graduates described how capacity growth influenced seven individual capabilities and their ability to take collective or shared actions in three areas. Further, they described their ability to influence changes in conditions in three areas critical public health: health equity, social determinants of health, and prevention.ConclusionEvaluating longer-term outcomes and impacts of capacity building interventions is crucial to both improve and justify public health workforce development initiatives, particularly as prevention and population health needs persist. We posit that evaluations will be more effective if standardized methods are used across interventions, and if there is a greater push to share and publish results. We present a conceptual framework that may inform and guide future evaluation and process improvement efforts.